Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm supposed to show that:

$$y=\frac{5(x-1)(x+2)}{(x-2)(x+3)} = P + \frac{Q}{(x-2)} + \frac{R}{(x+3)}$$

and the required answers are: $$ P=5, Q=4, R=-4 $$

I tried to solve this with partial fractions like so:

$$5(x-1)(x+2) = A(x+3) + B(x-2)$$

$\implies$ $A$=4, $B$=-4
$\implies$ $Q$=4, R=-4

But where does $P$=5 come from?

Or should I have first multiplied out the numerator and denominator and then used long division to solve?

share|improve this question
3  
You can find some good starting points on how to format mathematics on the site here. This AMS reference is very useful. If you need to format more advanced things, there are many excellent references on LaTeX on the internet, including StackExchange's own TeX.SE site. –  Zev Chonoles Mar 6 '13 at 10:51
2  
Yes, you should have done long division first. Look at that last displayed equation of yours --- quadratic on the left, linear on the right --- that can't possibly be right. –  Gerry Myerson Mar 6 '13 at 12:13
add comment

3 Answers

up vote 3 down vote accepted

$$\frac{5(x-1)(x+2)}{(x-2)(x+3)} = P + \frac{Q}{(x-2)} + \frac{R}{(x+3)}$$ gives
$$5(x-1)(x+2)=P(x-2)(x+3)+Q(x+3)+R(x-2)........(1)$$
Now put $x=2, x=-3,x=0$ respectively on both sides of $(1)$ to get, $Q=4,R=-4,P=5$ respectively. Hence you can reach the desired result.

share|improve this answer
    
Thanks... I wasn't sure if P was in the equation then what its denominator would be, but now it is clear I should have put P into the partial fractions calculations. –  Ozzy Mar 6 '13 at 13:35
    
@Ozzy You are welcome. –  user52976 Mar 6 '13 at 13:37
    
I would like to add that comparing the coefficients of x-squared terms gives P=5 directly –  Ozzy Mar 6 '13 at 13:53
    
@Ozzy Yes.You are right. Nice observation. –  user52976 Mar 6 '13 at 13:54
add comment

You are given the wrong expression. After some calculation I figure out that in order for these two expressions to be equivalent,

$$\frac{5(x-1)(x-2)}{(x-2)(x+3)} = 5 + \frac{4}{(x-2)} + \frac{-4}{(x+3)}$$

instead of having $\frac{5(x-1)(x-2)}{(x-2)(x+3)}$, it should be

$$\frac{5(x-1)(x+2)}{(x-2)(x+3)}$$

Now solve it again it would work well.

My approach to solving it is

$$\frac{5(x-1)(x+2)}{(x-2)(x+3)} = \frac{5x^2+5-10}{(x-2)(x+3)} =\frac{\frac{5x^2+5-10}{(x-2)}}{(x+3)}$$

$$\frac{\frac{5x^2+5-10}{(x-2)}}{(x+3)} = \frac{5x+15+\frac{40}{(x-2)}}{(x+3)}$$

$$\frac{5x+15+\frac{40}{(x-2)}}{(x+3)} = 5+\frac{40}{(x-2)(x+3)}$$

$$5+\frac{40}{(x-2)(x+3)}=5 + \frac{4}{(x-2)} + \frac{-4}{(x+3)}$$

share|improve this answer
    
I'm sorry that was a typo, but you are correct that it was (x+2) not (x-2). I can't really follow your calculation steps... I think you are doing the long division and partial fractions at the same time? –  Ozzy Mar 6 '13 at 13:39
    
@Ozzy I expand it first then do two long devisions before doing a simple partial fraction expansion. –  0arch Mar 6 '13 at 14:48
add comment

You don't need to do any long division. In the expression

$$y = \frac{N(x)}{D(x)} = \frac{5(x-1)(x+2)}{(x-2)(x+3)}$$

The numerator $N(x) = 5(x-1)(x+2)$ and denominator $D(x) = (x-2)(x+3)$ are polynomials of degree $2$. Since the roots of $D(x)$ are simple, $y$ can be rewritten in the form:

$$y = P(x) + \frac{Q}{(x-2)} + \frac{R}{(x+3)}$$

where $P(x)$ is a polynomial of degree $\deg N(x) - \deg D(x) = 2 - 2 = 0$, i.e. a constant. To evaluate the 3 coefficients, you can evaluate both side at 3 different values of $x$: the two roots of $D(x)$ and $\infty$:

$$\begin{align} P &= \lim_{x\to\infty} \frac{N(x)}{D(x)} = 5\\ Q &= \lim_{x\to 2} (x-2)\frac{N(x)}{D(x)} = \lim_{x\to 2}\frac{5(x - 1)(x+2)}{x+3} = \frac{5(2 - 1)(2+2)}{2+3} = 4\\ R &= \lim_{x\to -3}(x+3)\frac{N(x)}{D(x)} = \lim_{x\to-3}\frac{5(x-1)(x+2)}{x-2} = \frac{5(-3-1)(-3+2)}{-3-2} = -4 \end{align}$$

share|improve this answer
    
Loving it.. This is how it should be done. –  0arch Mar 6 '13 at 14:50
    
Nice... wasn't taught this method –  Ozzy Mar 8 '13 at 6:53
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.